Caracterização tribológica do revestimento ta-C/DLC (carbono tipo diamante/ amorfo tetraédrico não hidrogenado) sobre aço ABNT 52100 em contato e movimento relativo com esfera de Si3N4 - David Jonhson Barcelos (2019)
DLC (Diamond-like Carbon) coatings are thin films formed by carbon of sp2 and sp3 bonds in different proportions and have as main characteristics their low coefficient of friction, high hardness, chemical inertia, biological compatibility, optical transparency and electrical insulation. The tetrahedral DLC hydrogen-free (ta-C) is composed of big proportions of sp3 bonds that improve its properties. This work proposes a deepening in the study of the coefficient of friction and mechanical wear of the tetrahedral amorphous carbon hydrogenfree (ta-C) DLC in contact with ceramic material (Si3N4) in order to evaluate its behavior, and compare it with the uncoated substrate (ABNT 52100 steel) in contact with the same material. To reduce the negative effect of contaminants on lubricating oils, or even reduce friction in situations of difficult lubrication, DLC coating can be applied to surfaces of dry materials with reduction of the coefficient of friction, high creep and increase wear resistance durability of the components. The effect of the ta-C/DLC surface coating on the resistance to friction and wear was studied from tests carried out on a pin-on-disk tribometer in a dry environment and at room temperature. The ta-C/DLC obtainment was made by methods based on PVD (Physical Vapor Deposition) cathodic arc evaporation with ~1.5 m thick on ABNT 52100 steel substrate. The behavior of the friction and wear of the DLC film, and also the ABNT 52100 steel were evaluated against silicon nitride beads with contact pressure, and relative movement. The characterization of the DLC film before the tribological assay was performed from SEM, EDS, scratch test, profilometry, nanoindentation and Raman spectroscopy. Then, the worn surfaces of the body and underbody were analyzed by means of profilometry and SEM. The friction and wear results for the dry film in contact with silicon nitride (Si3N4) were very significant, with friction values between 0.03 and 0.05 for high load and low load respectively, also indicating mild abrasive wear. However, the ABNT 52100 steel surface in contact with silicon nitride (Si3N4) obtained higher coefficient of friction values for the same conditions (between 0.65 and 0.825) and severe wear.